Protein kinase and ribonuclease domains of IRE1 confer stress tolerance, vegetative growth, and reproductive development in Arabidopsis - Yan Deng; Renu Srivastava; Stephen H. Howell (2013)
Significance Previous studies showed that the unfolded protein response (UPR) in plants is elicited by environmental stress, but not that it protects plants from stress. This paper demonstrates by blocking both arms of the UPR signaling pathway that the UPR protects plants from stress and supports growth and development. IRE1 is a key component of the UPR signaling pathway and has dual protein kinase (PK) and RNase activities. We showed that both the PK and RNase activities, but not its normal splicing target, bZIP60 mRNA, are required for root growth and male gametophyte development, while both RNase activity and bZIP60 are required for endoplasmic reticulum stress tolerance.